OPTIMALISASI PENGELOLAAN PERKEMBANGAN SOSIAL EMOSI ANAK USIA DINI - Khulusinniyah; Farhatin Masruroh (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
The social-emotionaldevelopment of children is important to be developed from an early age. The emotionaldevelopment in early childhood, takes place simultaneously with their social development. Even there is claim that their emotional development is influenced by their social development. Itcaused by the emotional reactions displayed by early childhood as a response to the social relationships that they live with other people. The emotional development of early childhood can also affect the sustainability of social relationships. Stimulation is an important thing to give by early childhood educators and parents so they can optimize their social emotion development. With this treatment, they can grow into the life ready person in facing the complex future.